Mechanically reclaiming abandoned saline soils: a numerical evaluation - Prathapar, Sanmugam A.; Qureshi, Asad Sarwar (International Water Management Institute, 1999)
Tests the hypothesis that timely surface cultivation before monsoon or winter rains in semiarid and arid areas will assist reclamation of abandoned saline soils. The effect of surface cultivation, monsoon rains, depth to water table, and ground water salinity on secondary salinity are evaluated using a numerical model, SWAP93.